During the Pandemic Perceived Quality Forms Customer Loyalty via Brand Equity Oppo Smartphone Users - Ade Onny Siagian; Dodi Prasada; Agus Sudarsono; Hadion Wijoyo (UPT Penerbitan Universitas Jember, 2021)
This study aims to determine whether during the pandemic Perceived Quality has an effect on Customer Loyalty through Brand Equity on Oppo brand smartphone users in the Depok area. By using a quantitative research approach and SEM factor analysis methods as well as SPSS Amos 23 test equipment. The object of the analysis is consumers